2015
DOI: 10.3171/2014.10.jns14502
|View full text |Cite
|
Sign up to set email alerts
|

Survival in patients treated for anaplastic meningioma

Abstract: A lthough meningiomas are the most common primary brain tumor, the anaplastic variant is exceedingly rare, accounting for 1%-3% of all meningiomas. 16 These tumors display frankly anaplastic histology with an undeniably malignant clinical course. Median overall survival (OS) has been reported as 1.5 years, 28 with 5-year survival ranging from 47% to 61%. 6,11,30,32 Given the rarity of this meningioma variant and scarcity of literature, relatively little is understood with regards to the underlying pathogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
41
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 39 publications
5
41
1
Order By: Relevance
“…17,21 The univariate association of increased postdischarge seizure occurrence in males may be due to gender differences in tumor characteristics. Male gender has been associated with more aggressive disease in anaplastic meningioma, 24 greater incidence of severe complication in intracranial meningioma surgery, 25 and in our study, higher grade tumors.…”
Section: Discussionsupporting
confidence: 63%
“…17,21 The univariate association of increased postdischarge seizure occurrence in males may be due to gender differences in tumor characteristics. Male gender has been associated with more aggressive disease in anaplastic meningioma, 24 greater incidence of severe complication in intracranial meningioma surgery, 25 and in our study, higher grade tumors.…”
Section: Discussionsupporting
confidence: 63%
“…This finding was not surprising, as radiotherapy has been shown to upregulate PD-L1 in other tumor types, likely through release of interferon-gamma [24]. In a recent report, Moliterno et al, based on a retrospective series, observed that de novo grade III tumors seem to have more favorable survivals compared to those that progressed from a lower grade tumor, independent of extent of resection [25]. In our cohort, although prior treatment status correlated with higher PD-L1 expression, PD-L1 expression on CD68− cells was significantly predictive of poor overall survival while recurrent status alone was not.…”
Section: Discussionmentioning
confidence: 99%
“…13 For WHO grade 3 tumors, several reports showed that a combination therapy increases survival. [23][24][25] Cao et al noted that for WHO grade 3 tumors, no significant difference in progression-free survival between patients with and without radiotherapy. However, radiotherapy was associated with a longer overall survival with a median duration of 89 versus 42 months without radiotherapy.…”
Section: Discussionmentioning
confidence: 99%